Rompre le tabou de l’hétérosexualité, en finir avec la différence des sexes : les apports du lesbianisme comme mouvement social et théorie politique - Jules Falquet (Genre, Sexualité et Société)
Feminist lesbianism goes much beyond individual sexual practices. It is examined here as a social movement that has produced theoretical insights, from the 1970s and 1980s onward, which deserve to be further publicized. This article will consider various theories, notably Nicole-Claude Mathieu’s research in relation with the various conceptualizations of the relationship between sex, gender and sexuality; as well as the works of the Combahee River Collective on the intersectionality of power relations linked to sex, « race », class and sexuality, and their implication on the politics of alliances among and within social movements. Exploring the analysis put forward by Adrienne Rich and Monique Wittig, among others, will help to move beyond the struggles focusing on bodily alteration and/or the transformation of the individuals’ sexual and social roles. These works provide alternatives to question, and collectively undermine heterosexuality as an institution that legitimizes sex as a social relation of power. To conclude, I explore the usefulness of these theoretical tools to analyze and oppose social power relations based on sex, sexuality, « race » and class.